A review of potential routes to zero and negative emission technologies via the integration of renewable energies with CO2 capture processes. (March 2023) - Quang, Dang Viet; Milani, Dia; Abu Zahra, Mohammad
Highlights: The potential integration routes of CO2 capture technologies with renewables are discussed. Renewable energies can play a vital role to achieve net-zero or negative CO2 emissions. Novel capture processes may address the intermittent nature of renewable energy sources. Renewable integration could minimize/stop carbon capture retrofits from steam consumption. Net-zero emission target would be realizable by leveraging negative emission technologies. Abstract: This paper broadly reviews the integration of different renewable energy sources including solar, bioenergy, wind, and geothermal energy with CO2 capture processes and evaluates the possible contribution to achieve net-zero or negative CO2 emissions. Each renewable energy integration option possesses advantage points, which may help reducing the CO2 capture cost and potentially realize the net-zero or negative emission ambitions. In power sector, renewable energy integration encounters a number of challenges such as high upfront investment, large fluctuation in the CO2 capture rate, and electricity cost. Nonetheless, those drawbacks can be minimized by flexible designs that would optimize renewable energy contribution with steam extraction to improve power plant efficiency and install on/off function to exploit low electricity price periods and to alleviate the effect of the intermittent nature of those renewable energy options. Although, many integration scenarios have been proposed in literature, there is a lack of consideration with recently advanced CO2 capture technologies in the hard-to-abate emission sectors such as heavy industries and heavy transport. Renewable energy integration may also bring a promising revenue to advance the ambitious goal of direct air capture (DAC) technologies due to the flexibility in location and operation modes, nevertheless, it draws a little attention. In this analysis, the advantages and disadvantages of each renewable energy source when it is integrated into a CO2 capture process are discussed and thereby potential research directions are identified. It is emphasized that renewable energy integration could autonomize carbon capture retrofits to provide convenience to power/industrial plant operators and/or to realize the ambitions of installing independent and scalable DAC systems on inexpensive land or in vicinity of the CO2 storage/utilisation sites.